The Effect of Motor Pathway Control As A Style For Learning Some Basic Skills In Floor Exercises In Men’s Gymnastics - Ahmed, Nazm (Journal of Physical Education, 2017)
The aim of the research is using motor pathway control as a teaching style through using exercise according to performance indicators. The researcher used the experimental method. The subjects were (40) sophomore students of physical education and sport Sciences College. The exercises were designed according to proposed style for the skills. The data was collected and treated using proper statistical operations. The researcher concluded that controlling motor pathway affects using motor abilities and concentration on compound muscular groups as well as controlling the motor pathway achieves better position for body center during practice. Finally the researcher recommended using motor pathway control on freshmen and during the first stages of learning and training as well as using it for developing special muscular groups and to reduce the variables affecting using mental abilities.